Effect Of NAFTA On The Economics Of Mineral Production (Society for Mining, Metallurgy & Exploration, 1997)
The implementation of NAFTA in January 1994 was expected to have small but beneficial effects on the Mexican economy, mostly through increased investments. Mexico's mining industry was especially likely to benefit, as mineral investment funds would be diverted to the now safer Mexico and away from similarly endowed but more risky Latin American mineral economies. The results during the past two years have shown that it is government and macroeconomic factors that influence investment flows, rather than the fine tuning of trade flows through so called 'free-trade" agreements.